The influence of schedules of open office occupants’ presence on building’s energy demand - Bielskus, Jonas; Motuzienė, Violeta (International Conference “Environmental Engineering”, 2020)
Many studies show, that there is a difference between actual and design energy consumption in energy efficient and sustainable buildings. As a rule, buildings consume more energy than it has been foreseen at the design stage. Occupants’ behaviour in buildings is also identified as one of the main reasons causing the so called Performance Gap. Having mobile workstations, opened plan offices are becoming more popular in design solutions in sustainable buildings. Here we have studied one of such office spaces. Monitoring of real occupancy was performed and real occupation schedules were statistically generated. The schedules were compared to the ones given by European Standard for energy performance calculation as well as with default schedules proposed by simulation software DesignBuilder. The comparison shows a significantly lower measured occupancy compared to the above-mentioned schedules. To compare the influence of occupancy related assumptions on predicted energy demand, DesignBuilder model was created and simulated for 3 different occupancy schedules. The results have shown that primary energy demand of a building due to assumptions related with an occupancy, compared to default DesignBuilder schedules are: 111 kWh/m² (32%) higher than the standard case and 152 kWh/m² (44%) than the actual one.
Keywords: passive occupants’ behaviour; open plan office; schedules; Performance Gap; energy simulation